2020
DOI: 10.1097/mcg.0000000000001446
|View full text |Cite
|
Sign up to set email alerts
|

Low Risk of Neoplasia and Intraprocedural Adverse Events in Gastric Hyperplastic Polypectomy

Abstract: Goals: Assess neoplasia and polypectomy-related adverse event (AE) rates in gastric hyperplastic polyps (GHPs). Background: GHPs carry a risk of neoplastic transformation. The rate of neoplastic transformation and the risk of polypectomy-related bleeding are unclear in the West, as data are derived from Asian or small studies. The authors aimed to determine the rate of dysplasia and intraprocedural AEs in GHP polypectomies in a western cohort. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Second, to the best of our knowledge, there is no study addressing complications on gastric polypectomy between HSP and CSP. There were only limited studies ever reported low adverse effects in gastric polypectomy based on specific histology 21,27 . Our research provided more complete aspects regarding to the risk factors of gastric polypectomy.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Second, to the best of our knowledge, there is no study addressing complications on gastric polypectomy between HSP and CSP. There were only limited studies ever reported low adverse effects in gastric polypectomy based on specific histology 21,27 . Our research provided more complete aspects regarding to the risk factors of gastric polypectomy.…”
Section: Discussionmentioning
confidence: 79%
“…There were only limited studies ever reported low adverse effects in gastric polypectomy based on specific histology. 21,27 Our research provided more complete aspects regarding to the risk factors of gastric polypectomy. A variety of risk factors were taken into consideration in the regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to take multiple biopsies of the intervening mucosa to ensure proper diagnosis and treatment. In the study by Bar et al, the malignant transformation rate for GHPs was 1.9%, which was lower than the literature [27]. Since the etiology of relapse is still unclear, long-term follow-up seems necessary to detect and treat relapses to prevent poor outcomes in cancer transformations.…”
Section: Discussionmentioning
confidence: 82%